Investigating the relationship between personality dimensions, level of self-efficacy and perceived performance appraisal satisfaction: a case for individualised performance appraisals - Milosevich, Jodi (Organisational Psychology, 2020)
Orientation: For decades, organisations have implemented performance management systems in order to promote an environment focused on performance enhancement and employee development. Performance appraisals have consistently been at the centre of performance management systems. However, they are often perceived as being ineffective or unsatisfactory, resulting in dissatisfaction and contributing to financial and time losses. Performance Appraisal Satisfaction (PAS) amongst employees is, therefore, vital if organisations want to achieve desired outcomes. Limited research was found that explained or described methods which organisations can utilise to increase PAS amongst employees. Research rationale and objectives: As organisations become more global, innovative and employee-focused, the need to cater to individual needs and desires has significantly increased. This study aimed to investigate ways in which PAS can be increased through the individualisation of three performance appraisal aspects namely; number of raters; method of feedback and frequency of feedback. In terms of the individualisation factors, this study has focused on; level of perceived self-efficacy and the Big Five personality dimensions. Research approach: Given the limited pre-existing literature on this topic, the present study used an exploratory research approach to engage with the results in an in-depth manner. Qualitative and quantitative data was collected from employees and Human Resource practitioners in order to establish performance appraisal preferences and the viability of implementing individualised performance appraisals. Composite questionnaires consisting of Likert-type questions, choice-based conjoint tasks and open-ended questions, were distributed utilising a convenient and snowball methodology. Completed questionnaires were analysed by means of descriptive and inferential and statistics, conjoint analysis, as well as by means of a thematic analysis. Semi-structured interviews were conducted with Human Resource practitioners and analysed using a thematic analysis. Main findings: Results from the descriptive and inferential statistics indicate that the level of self-efficacy and personality-type are significant in predicting certain performance appraisal preferences. For example, respondents with increased levels of perceived self-efficacy significantly preferred face-to-face feedback from a manager (p < .05) while respondents with low levels of perceived self-efficacy significantly preferred impersonal feedback (p < .05). Results from the composite questionnaire’s open-ended items indicated that employees prefer performance appraisals which considered their personality type and level of self-efficacy. However, the thematic analysis conducted on the HR practitioner interviews revealed that HR practitioners are hesitant to implement a novel performance appraisal system for reasons including; gaining top-management support and the additional time and administrative burden it would likely impose on the HR practitioners themselves.